Digit ratio in the common spadefoot toad Pelobates fuscus (Anura: Mesobatrachia: Pelobatidae): patterns and correlations - M. Frątczak; M. Kaczmarski; Ł. Jankowiak; J. Klessa; K. Bielicki; B. Lyskov; P. Tryjanowski (The European Zoological Journal)
Digit ratio (DR or 2D:4D), an indicator based on the relative length of the second and fourth digits, has been linked to embryonic sex hormone levels and is regarded as a biomarker for ontogenetic changes and evolutionary traits across species. While DR patterns often display a sex bias, they vary among taxa: in most mammals and tailed amphibians, females exhibit higher 2D:4D ratio than males, whereas in birds and reptiles, the trend is reversed. However, data on DR in Anuran amphibians remains limited, particularly within the Mesobatrachia, a relatively primitive group. This study investigates DR in the common spadefoot toad (Pelobates fuscus), a little-studied and secretive species, using 68 archival specimens, and two analytic approaches. In the simple correlation approach, there were no significant sex differences in DR in this species. However, when DRs were adjusted allometrically by digit length, regression analysis showed significant effects of both sex (male) and snout–vent length (SVL). Males had significantly larger DRs, mainly 2D:4D and 3D:4D, in all limbs, while SVL had a significant negative effect on most DRs. Further research is needed to clarify the factors influencing DR in amphibians.